The Important Role of Population and Samples in Educational Research - Iik Timamah; Halimatus Sa’diyah; Faiqatul Munawarah; Faridatul Jannah (Demagogi: Journal of Social Sciences, Economics and Education, 2025)
The aim of this research is to explain the important role of population and sample in educational research. This research uses conceptual methods with descriptive analysis to examine the important role of population and samples in educational research. The correct selection of population and samples greatly influences the quality and validity of research results. This research identifies common phenomena, such as errors in selecting unrepresentative samples, which result in research results that are inaccurate and difficult to generalize. In addition, limited resources and knowledge of modern sampling methods are challenges for researchers. Through a descriptive approach, this research discusses various types of populations and samples, as well as sampling techniques that can be applied in educational contexts. It is hoped that a deeper understanding of these aspects will make a significant contribution to the validity and accuracy of the research results.